Case Report: Poor Nutrition on the Patient's Cerebral Palsy - Putu Aryani; I Nengah Gandi Karyadi; Dyah Kanyawati (Faculty of Medicine, Public Health, and Nursing, 2019)
A 3-year-old boy was taken to a health center in the Karangasem regency, Bali, by his parents with complaints from the previous two weeks that the child could not sleep well, grew fussy because of the relapse of the seizure. Parents also complain that their children don't want to eat so him get thinner. Patient have been recorded since a year before suffering from malnutrition associated with their disability, namely cerebral palsy (CP). The patient has been diagnosed with CP since birth, where the patient was born twin, with very low birth weight (under 2500 grams), but his twin brother died when birth. Since the birth, the patient has been monitored by the puskesmas Nutrition Program Holder with weight has never increased.........